Review On the Biosynthesis of Composite TiO2 - Inorganic/Metal Oxide (Fe2O3): Photocatalytic and Antibacterial Purpose Of Wastewater Treatment - Johngika, Jaffner; Harun, Zawati (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Photocatalytic process has the ability of to degrade or reduce toxicity substance by chemical reaction and producing non-hazardous gasses to the environment has attract many researchers to apply this technology in treating waste water problem recently. There are many methods to synthesize the composite -, such as hydrothermal, sol-gel and ultrasonic impregnation methods, which will be described in this study for the comparison of which composite would have the highest rate of photocatalytic activity based on its synthesizing technique. In this research, the review of synthesized composite mixture of - will be investigated towards photocatalytic and antibacterial application. The analysis and comparison will be conducted based on phase analysis (XRD), Field Emission Scanning Electron Microscopy, FTIR analysis and UV–vis diffuse reflectance spectroscopy. Thus, the study will focus on the properties and performance analysis of composite inorganic particles in eliminating the mixture of organic pollution specifically for waste water treatment.